Sekolah Berbudaya Lingkungan: Integrasi Kebijakan, Kurikulum, dan Budaya Sekolah di SDN Tanggul Wetan 2 - Nailil Aniq; Erlin Indaya Ningsih (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2026)
This study aims to analyze the integration of policy, curriculum, and school culture in realizing an environmentally friendly school at SDN Tanggul Wetan 2. The study used a qualitative approach with a case study type. The research subjects included the principal, teachers, students, program coordinators, and parents. Data collection techniques were carried out through observation, in-depth interviews, and documentation. Data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results showed that the school policy has integrated environmental care values ​​through the Adiwiyata program supported by external partnerships and periodic evaluations. The curriculum implementation was carried out contextually by integrating environmental materials into various subjects and using project-based learning methods. School culture is realized through habituation of activities such as community service, waste sorting, and energy saving which have an impact on changes in student behavior. Supporting factors include the principal's leadership, teacher participation, parental support, and the school environment, while inhibiting factors include the lack of consistent student habits. Thus, the integration of policy, curriculum, and school culture has proven to be key in building a sustainable environmentally friendly character.